2013
DOI: 10.1167/iovs.13-12437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Contact Lens–Induced Changes in Keratoconic Corneas Using In Vivo Confocal Microscopy

Abstract: Significant corneal microstructural abnormalities were observed in eyes with keratoconus. RGP contact lens wear was associated with a further reduction in the basal epithelial cell and anterior stromal keratocyte densities, but with no effect on posterior stromal keratocyte density, endothelial cell density, or corneal nerve morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
2
24
1
Order By: Relevance
“…Consequently, it is a common subject for evaluation when investigating the impact of ocular and systemic diseases on corneal innervation, such as in dry eye, 5 infectious keratitis, 6 and keratoconus. 7 In addition, quantification of the SBNP morphology is seen as a potential ophthalmic marker for the detection of diabetic peripheral neuropathy. 8,9 Furthermore, studies have analyzed nerve regeneration in the SBNP as an indicator of corneal recovery following surgical refractive correction and other ocular surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is a common subject for evaluation when investigating the impact of ocular and systemic diseases on corneal innervation, such as in dry eye, 5 infectious keratitis, 6 and keratoconus. 7 In addition, quantification of the SBNP morphology is seen as a potential ophthalmic marker for the detection of diabetic peripheral neuropathy. 8,9 Furthermore, studies have analyzed nerve regeneration in the SBNP as an indicator of corneal recovery following surgical refractive correction and other ocular surgery.…”
Section: Introductionmentioning
confidence: 99%
“…IVCM studies have consistently demonstrated lower keratocyte density in keratoconus compared to healthy corneas . This observation may be associated with the proposed contribution of keratocyte apoptosis to the pathogenesis of keratoconus .…”
Section: In Vivo Confocal Microscopymentioning
confidence: 83%
“…IVCM has revealed that both anterior and posterior keratocyte density is reduced in keratoconus compared to controls . Interestingly, CL‐wearing keratoconics have been demonstrated to have a significantly lower anterior keratocyte density than keratoconics who did not wear CLs . However, posterior keratocyte density does not appear to be affected by the use of CLs in patients with keratoconus …”
Section: In Vivo Confocal Microscopymentioning
confidence: 99%
“…2224,31,32 In addition, the decline in keratocyte density has been shown to correlate with disease severity. 24,25 By carefully comparing IVCM images with images from SD-OCT, FFOCM, and histology, we were able to improve our 3D understanding of the tissue and better interpret the IVCM data, allowing us to identify features illustrated in Figures 1–3, such as flattened basal epithelial cells, hyperreflective ferritin deposits in basal epithelial cells, damage to basement membrane and BL, and stromal scarring in IVCM images.…”
Section: Discussionmentioning
confidence: 99%